Non-invasive measurement of faecal glucocorticoid metabolites in Upland Geese Chloephaga picta - Koch, Martina; Möstl, Erich; Steinmetz, Hanspeter W.; Clauss, Marcus; Masello, Juan F.; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2009)
Glucocorticoid (GC) hormones rise in response to stressors, including natural events including weather or predator presence, and human activities, such as hunting, scientific research or recreational visits. However, because blood sampling itself causes stress and is dangerous or even impossible in some wildlife species, feedback-free methods for GC determination are needed to assess stress in these animals. Faecal GC analyses have thus gained interest. Here, we validate a non-invasive method to estimate the physiological stress in the Upland goose Chloephaga picta. An adrenocorticotropin hormone (ACTH) challenge was conducted in captive adults (female and male), and droppings were collected before, during and after the experiment. Corticosterone metabolite (CM) secretion in response to the ACTH challenge was measured with several enzyme immunoassays (EIA) to find the most appropriate test. We used CM levels during the periods before and after the experiment as control data. An EIA for 11-oxoetiocholanolone achieved the highest response to the ACTH challenge and also reflected a stress response to unfamiliar environment. Furthermore, CM concentrations of dry samples were highly correlated with the corresponding non-dried (frozen) samples. The data suggest that this method is appropriate to measure the stress in Upland geese, and that samples can be stored either frozen or dry form.
Keywords: Chloephaga picta; Conservation biology; Corticosterone metabolites; Non-invasive endocrine monitoring; Stress; ddc:570; ddc:590